Therapeutic outcome of patients with Lennox–Gastaut syndrome with mitochondrial respiratory chain complex I deficiency - Na, Ji-Hoon; Lee, Young-Mock (Frontiers in Neurology, 2024)
Background: Lennox-Gastaut syndrome (LGS), a severe developmental epileptic encephalopathy, has various underlying causes. Mitochondrial respiratory chain complex I (MRC I) deficiency is an important cause of metabolic disorders such as mitochondrial dysfunction that can compromise brain function, thereby causing intractable epilepsy, including LGS. Thus, it can be expected that the presence or absence of MRC I deficiency may affect the treatment outcome of patients with LGS.In this retrospective study, we aimed to investigate differences in the epilepsy characteristics and treatment outcomes between patients with LGS with and without MRC I deficiency.We retrospectively reviewed the medical records of 92 patients with LGS. We divided 68 patients with LGS according to the presence (n = 30) or absence (n = 38) of MRC I deficiency and compared their epilepsy characteristics.Results: Generalized tonic and drop seizures were significantly worse in patients with LGS and MRC I deficiency than in those without MRC I deficiency group at the 1-year follow-up (p < 0.001) and final follow-up 1 (p < 0.001). Patients with LGS and MRC I deficiency had significantly fewer electroencephalogram (EEG) improvements compared to those without MRC I deficiency at the 1year follow-up (p = 0.031). Additionally, in the final follow-up period, patients with LGS and MRC I deficiency had significantly less improvement in EEG findings compared to patients without MRC I deficiency (p < 0.001).The overall treatment prognosis-in terms of improvement in traumatic generalized tonic seizure, drop seizure, and EEG findings-is worse in patients with LGS and MRC I deficiency than that in patients with LGS but without MRC I deficiency. Additional and targeted treatment is required to treat LGS with MRC I deficiency.